2002
DOI: 10.3928/0098-9134-20020901-09
|View full text |Cite
|
Sign up to set email alerts
|

Using Family-Style Meals to Increase Participation and Communication in Persons with Dementia

Abstract: Although researchers stress the importance of encouraging independent behavior in persons with dementia, institutional practices often foster dependence. This study took place in a six-resident locked dementia care unit that followed the common institutional practice of serving meals on prepared plates. The purpose of this study was to examine if changing the mode of meal delivery to "family-style," where residents were presented with serving bowls and empty plates, would increase resident communication and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 25 publications
4
102
0
Order By: Relevance
“…Several authors dealing with populations from different countries-Sweden, Norway, England, United States-have implemented mealtime routine alterations with people with dementia and have found positive outcomes such as enhanced communication, weight increase, autonomy, and quality of life (Althus, Engleman, & Mathews, 2002;Davis, Byers, Nay, & Koch, 2009;Mamhidir, Karlsson, Norberg, & Mona, 2007;Zgola & Bordillon, 2003). Depending on the culture of origin, authors suggested that opportunities to drink a glass of wine before the meal, to adopt family-style meals, or even to enjoy finger food can be advantageous.…”
Section: Cultural Standpoint Of Mealsmentioning
confidence: 96%
“…Several authors dealing with populations from different countries-Sweden, Norway, England, United States-have implemented mealtime routine alterations with people with dementia and have found positive outcomes such as enhanced communication, weight increase, autonomy, and quality of life (Althus, Engleman, & Mathews, 2002;Davis, Byers, Nay, & Koch, 2009;Mamhidir, Karlsson, Norberg, & Mona, 2007;Zgola & Bordillon, 2003). Depending on the culture of origin, authors suggested that opportunities to drink a glass of wine before the meal, to adopt family-style meals, or even to enjoy finger food can be advantageous.…”
Section: Cultural Standpoint Of Mealsmentioning
confidence: 96%
“…In conclusion, only eight quantitative studies (Li et al, 2012;Edvardsson, 2014;Marventano et al, 2015;Wetzels et al, 2010;Crespo et al, 2011;Black et al, 2012;Terada et al, 2012;Monteiro et al, 2014 ) are considered to be as high quality, which meet all the quality criteria. Five articles were considered to be low-quality articles (Altus et al, 2002;Winzelberg et al, 2005;Hodgson et al, 2014;Heggie et al, 2011;Banerjee et al, 2005), as they only meet one or two criteria (See Table 1). The quality of the remaining 26 studies are judged as moderate.…”
Section: Quality Of the Literature For Reviewmentioning
confidence: 99%
“…Yet simply making changes to the design of the dining room and how food is served does not ensure that the dining experience will be pleasant, or that the social side of eating will be enhanced. Much depends on the way staff interacts with residents and how they facilitate conversation at the table (17,18). Pleasant dining experiences are created when staff value the social aspect of meals and find ways to honor residents as individuals.…”
mentioning
confidence: 99%